Morphology and natural history of the cryptogenic sponge associate Polydora colonia Moore, 1907 (Polychaeta: Spionidae) - David, Andrew A.; Williams, Jason D. (Journal of Natural History, 2012)
The polychaete Polydora colonia is a widely distributed symbiont of sponges that has been reported as introduced into the Mediterranean Sea. Polydora colonia is re-described based on specimens associated with the sponges Microciona prolifera and Halichondria bowerbanki from New York and aspects of its reproduction and feeding biology are described for the first time. The morphology of P. colonia agrees with previous reports of this species. Females of P. colonia deposited egg capsules (14-19 eggs/capsule) in their tubes on sponges and adelphophagy was observed. Larvae appear to be competent to settle on hosts at the 13-chaetiger stage. One commensal ciliate and one parasitic copepod were found associated with P. colonia. P. colonia as an introduced species is evaluated based on current evidence. Sponge material was observed in the gut of >50% of the worms examined but further studies are needed to evaluate whether P. colonia is selectively feeding on M. prolifera.
World Polychaeta Database (WPolyDb)